Swap Book Risk Valuation Using Convexity Adjustments - Lim, Kian Guan (Institutional Knowledge at Singapore Management University, 2002)
Since the early 1980s, interest rate swaps have risen to become one of the most widely traded financial market instruments on the globe. The pervasive use of this financial instrument in managing interest rate and currency risks not only in America and Europe, but also in Asia, has implied a large swap book in most banks and in increasing attention paid to the risk valuation of such swap positions. In Asia, however, swap rates for contracts with tenors or maturities below five years are not as liquid as exchange traded Eurodollar futures. Therefore, Eurodollar futures prices are used to estimate forward positions traded in the OTC market. The use of Eurodollar futures prices to adjust for forward rates, commonly known as convexity adjustment, is shown via various methods for comparison. Both the industry favored Dean Witter Reynolds model and the increasingly popular term structure theoretic models such as Hull-White and Ho-Lee models are discussed.